THE INFLUENCE OF BUSINESS WITH CONTENT ECOMMERCE ON RETAIL BUSINESS TO THE ASPECT MARKETING OF MICRO SMALL MEDIUM IN DEPOK - Haryono, Sugeng; Nurlaela, Nurlaela (The International Journal of Business Review (The Jobs Review), 2018)
There are many factor that affect the rapid development of online busniness in Indonesia among the more eccommerce users. Associated with this researcher will examine about the influence of business with content ecommerce on retail business to theÂ  aspect marketing of micro small medium in Depok. Specific objectives of this research are 1). To help retail business managers maximize distribution, information and product socialization to be easily accessible by the community so as to be able to compete with business managers with ecommerce content. 2). the process of socialization, product education, marketing and product data processing through e-commerce. As for the results of the research, there is a significant effect of e-commerce content on retail business on the marketing aspect of Â Micro Small Medium in Depok